Hydrophobic interaction adsorption of whey proteins: effect of temperature and salt concentration and thermodynamic analysis - Minim, Luis A.; Bonomo, Renata C. F.; Coimbra, Jane S. R.; Fontan, Rafael C. I.; Silva, Luis H. Mendes da; Minim, Valéria P. R. (Journal of Chromatography B, 2006)
The adsorptive behavior of bovine serum albumin (BSA) and β-lactoglobulin (β-lg) on hydrophobic adsorbent was studied at four temperatures and different salt concentrations. The Langmuir model was fitted by experimental equilibrium data showing that an increase in temperature and salt concentration results in an increase on the capacity factor of both proteins. A thermodynamic analysis coupled with isotherm measurements showed that salt concentration and temperature affected the enthalpic and entropic behavior of the adsorption process of both proteins, mainly to the β-lg. The fast variation in the Z value for temperature over than 303.1 K suggest a great conformational change occurring in the β-lg structure, which almost duplicated the maximum adsorption capacity of this protein.
Keywords: Bovine serum albumin; β- Lactoglobulin; Thermodynamic parameters; Isotherm; Hydrophobic interaction